Modelling of Fabry-perot interferometer / Adibah Mohammad Nor - Mohammad Nor, Adibah (2012)
Interferometric device called Fabry Perot interferometer. A Fabry - Perot Interferometer is an optical interferometer in which a beam of light undergoes multiples reflections between two reflecting surfaces.